Islamic religious education for children of Indonesian migrant workers: adaptive strategies at the Indonesian school guidance center in Kuala Lumpur, Malaysia - Robbani, Ikbar; Muliyah, Pipit (UIR Press, 2026)
This study aims to identify and analyze various adaptive strategies in teaching Islamic Religious Education (IRE) at Sanggar Bimbingan (SB) in the Kuala Lumpur area, Malaysia. Undocumented children of Indonesian Migrant Workers (PMI) face massive structural marginalization that closes their access to formal education. In these highly limited conditions, Sanggar Bimbingan serves as a crucial alternative educational space to prevent the